Influence of spino-pelvic and postural alignment parameters on gait kinematics - Otayek, Joeffroy; Bizdikian, Aren Joe; Yared, Fares; Saad, Eddy; Bakouny, Ziad; Massaad, Abir; Ghanimeh, Joe; Labaki, Chris; Skalli, Wafa; Ghanem, Ismat; Kreichati, Gaby; Assi, Ayman (Gait & posture, 2020)
•To study the Influence of postural alignment parameters on gait kinematics.•134 asymptomatic adults had gait analysis & postural parameters assessed on X-rays.•Increase in sagittal vertical axis is related to larger knee flexion in stance.•Increase in radiological pelvic tilt is related to reduced pelvic obliquity.•Increase in thoracic kyphosis is related to reduced hip sagittal mobility. Postural alignment is altered with spine deformities that might occur with age. Alteration of spino-pelvic and postural alignment parameters are known to affect daily life activities such as gait. It is still unknown how spino-pelvic and postural alignment parameters are related to gait kinematics. To assess the relationships between spino-pelvic/postural alignment parameters and gait kinematics in asymptomatic adults. 134 asymptomatic subjects (aged 18–59 years) underwent 3D gait analysis, from which kinematics of the pelvis and lower limbs were extracted in the 3 planes. Subjects then underwent full-body biplanar X-rays, from which skeletal 3D reconstructions and spino-pelvic and postural alignment parameters were obtained such as sagittal vertical axis (SVA), center of auditory meatus to hip axis plumbline (CAM-HA), thoracic kyphosis (TK) and radiologic pelvic tilt (rPT). In order to assess the influence of spino-pelvic and postural alignment parameters on gait kinematics a univariate followed by a multivariate analysis were performed. SVA was related to knee flexion during loading response (β = 0.268); CAM-HA to ROM pelvic obliquity (β = −0.19); rPT to mean pelvic tilt (β = −0.185) and ROM pelvic obliquity (β = −0.297); TK to ROM hip flexion/extension in stance (β = −0.17), mean foot progression in stance (β = −0.329), walking speed (β = −0.19), foot off (β = 0.223) and step length (β = −0.181). This study showed that increasing SVA, CAM-HA, TK and rPT, which is known to occur in adults with spinal deformities, could alter gait kinematics. Increases in these parameters, even in asymptomatic subjects, were related to a retroverted pelvis during gait, a reduced pelvic obliquity and hip flexion/extension mobility, an increased knee flexion during loading response as well as an increase in external foot progression angle. This was associated with a decrease in the walking pace: reduced speed, step length and longer stance phase.